A Case of Spontaneous Multivessel Coronary Artery Spasm That Underwent Stent Implantation Accompanying ST Segment Elevation on Inferior Electrocardiographic Leads - Nuray Kahraman Ay; Muharrem Nasifov; Ömer Goktekin (Case Reports in Cardiology)
Coronary artery spasm is usually defined as a focal constriction of a coronary artery segment, which is reversible, and causes myocardial ischaemia by restricting coronary blood flow. A coronary spasm may rarely compromise all three epicardial arteries simultaneously. We present a case of severe coronary spasm afflicting all coronary arteries accompanying an ST segment elevation in leads D2-D3 and aVF.